Spaces of Articulation: Theorising Intersubjective Articulation in Encounters with Refugees in Post-Migrant Societies - Kaulertz, Monique (International Review of Theoretical Psychologies, 2026)
The word “articulation” is usually used to describe linguistic and other symbolic forms of meaning making (Schlette & Jung 2005, Jung 2009, Wilczek 2012). The meaning-making aspect of language and action is mostly privileged over the aspect of building relationships with others (Angehrn 2012). However, it is rarely taken into account that acts of articulation are not solitary actions of isolated individuals. They are often the direct result of social cooperation and dialogical communication. The ability to articulate something thus depends strongly on our relationships with others. The article argues for theorising a concept of articulation that takes this dependency and mediatedness into account. It therefore goes beyond an individualistic and monadic understanding of meaning-making and emphasises the aspect of articulations as being social acts. The ethnographic research on articulation on which this article is based analyses the researcher’s encounters with refugees in the asylum system during her time in the field. It asks how the articulations of experiences of suffering and violence can take place in “Spaces of Articulation” beyond a professional therapeutic setting or the asymmetrical context of the asylum hearing and explores principles of solidary communication and cooperation in the everyday life of people in “post-migrant societies” (Foroutan 2021).